CONTRASTIVE ANALYSIS OF THE CONCEPT OF "FAMILY" IN ENGLISH AND UZBEK LANGUAGES (American Journal of Pedagogical and Educational Research, 2023)
The concept of "family" is to reveal the factors that ensure the manifestation of the linguistic-cultural content at the lexical, phraseological, paremiological and text levels, and to scientifically justify the similarities and differences in the conceptual perception of family relations in the languages being used. To determine the linguistic essence of the concept of "family" and its role in language development; to reveal and describe the linguistic and cultural content of the concept of "family" in English and Uzbek languages in the material of lexicon, phraseology, paremiology and artistic texts; comparison of the conceptual basis of the lexemes "family" and "family" taking into account national and cultural characteristics; to determine the linguistic and non-linguistic factors that ensure the formation of linguistic units reflecting family relations in the life of English and Uzbek peoples; forming a classification of English and Uzbek terms expressing close blood kinship and distant kinship, matrimonial kinship and clan relations, distinguishing similarities and differences in groups of lexemes denoting family and kinship relationships of people in the compared languages.